Bagaimanakah Pengendalian Kecelakaan Kerja pada Pemasangan Pipa Pemadam Kebakaran di PT “PTC”? - Pipit Marfiana (Universitas Wiralodra, 2022)
Every year there are more than 250 million accidents in the workplace and more than 160 million workers get sick. In addition, 1.2 million workers died due to accidents. Occupational Health and Safety which has been popularly known as K3, and is widely spread in every industrial sector. Therefore, this study aims to describe the program, procedure, implementation, and control of work accidents in the installation of fire extinguishers at PT